CliffsTestPrep Cisco CCNA - Lammle, Todd (Wiley, 2007)
Written by test-prep specialists, this guide begins with a complete description of the exam, and then goes on to cover the four main areas that the test targets: planning and designing, implementation and operation, troubleshooting, and technology. The authors provide more than 500 practice questions with answers and explanations, share proven test-taking strategies, and offer ten full-length practice exams that are structured like the actual test so you’ll be familiar with the format.